E-023 Progressive occlusion in aneurysms treated with stent assisted coiling: flow diversion?. (16th November 2010) - Izar, B; Rai, A; Carpenter, J; Raghuram, K
Abstract : Background: Treatment of intracranial aneurysms using stent assisted coiling (SAC) has broadened the range of endovascular therapies for these aneurysms. Objective: Our goal was to assess the long term durability of SAC with specific attention to progressive aneurysm occlusion anecdotally observed in these patients. Materials and methods: A total of 84 aneurysms in 80 patients were initially assessed. Of these, 59 patients on whom long term follow-up was available were included. Immediate post-treatment and follow-up angiograms were evaluated by two independent observers and graded for aneurysm coil coverage (>95%; 85–95%, <85% of the aneurysm volume containing any loop of coil) and intra-aneurysmal flow (no flow, neck remnant, flow beyond the neck). Aneurysm morphology (spherical vs ellipsoid), orientation (sidewall vs bifurcation) and volume were also recorded, as was the packing density of the coil mass. Progressive occlusion was defined as decreased intra-aneurysmal flow or increased coil coverage on the follow-up angiogram. Results: The mean follow-up duration was 20.6 months (range 1.2–57.2 months). The mean aneurysm size was 8.4 mm (maximum dimension) and the mean packing density was 32.6%. On the initial treatment, >95% coil coverage was achieved in 81% of patients. On the immediate post-treatment angiogram, 71.1% of the patients had either no intra-aneurysmal flow or flow at the neck while 28.9% demonstrated flow beyond the neck. On the follow-up study, however, 91.5% of the patients had no flow or flow limited to the neck while the percentage of patients with flow beyond the neck was reduced to only 8.4%. Thus 35.6% (21/59) of patients demonstrated progressive reduction in the intra-aneurysmal flow on follow-up imaging. The most important predictor for progressive aneurysm occlusion was the aneurysm orientation; side wall aneurysms demonstrating a higher propensity for progressive occlusion than bifurcation aneurysms (p=0.02). This was independent from aneurysm volume, packing density and initial coil coverage. After orientation, aneurysm shape was the strongest predictor, with a spherical shape showing greater progressive occlusion than a complex or ellipsoid shape (p=0.05). Conclusion: Sidewall aneurysms with a relatively homogeneous shape have the greatest propensity of showing progressive aneurysm occlusion when treated with SAC. This could possibly be secondary to a higher degree of flow diversion seen in the side wall as opposed to bifurcation aneurysms. This is also important because in these aneurysms leaving a neck remnant or small amount of intra-aneurysmal flow as opposed to taking the added risk of complete occlusion by additional coils may be a safe choice.